Learn WatchKit for iOS - Topley, Kim (Apress : Imprint: Apress, 2015)
Learn WatchKit for iOS covers the development of applications for the new Apple Watch using the WatchKit framework in iOS 8 and the Swift programming language. In this book, an Apple Watch application is an extension to an existing iOS app and is packaged and submitted to the App Store along with it. Using a suite of simple examples, Kim Topley, co-author of Beginning iPhone Development with Swift, introduces and explains every feature of WatchKit and the associated technologies that you'll need to understand to build Apple Watch applications for iOS 8, culminating in a complete WatchKit application that shows weather forecast information for various cities around the world on the Apple Watch.